Karakterisasi Bakteri Kombucha Teh Melati dan Teh Hijau sebagai Agen Pupuk Hayati - Muhammad Fauzi; Nisa Ihsani; Rois Suriyah (Jurnal Biodiversitas dan Bioteknologi, 2024)
Production of fermented tea or kombucha can produce waste in the form of brown scoby. This waste can be used as a source of biological fertilizer agents for plants. This research aims to identify bacteria that act as biological fertilizer agents contained in kombucha scoby waste. The research method was the isolation and characterization of bacteria grown on Pikovskaya solid media to determine the biochemical reactions of groups of phosphate solubilizing bacteria and sedirophore bacteria on Fe-CAS media. The results of the research showed that there were phosphate solubilizing bacteria from samples K1 and K2 with the criteria that the colonies formed a clear clear zone (halozone) and K1 showed positive as a siderophore producing bacteria with orange colonies formed.